2(x-3)-3(4-2x)+x=

Simple and best practice solution for 2(x-3)-3(4-2x)+x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-3)-3(4-2x)+x= equation:


Simplifying
2(x + -3) + -3(4 + -2x) + x = 0

Reorder the terms:
2(-3 + x) + -3(4 + -2x) + x = 0
(-3 * 2 + x * 2) + -3(4 + -2x) + x = 0
(-6 + 2x) + -3(4 + -2x) + x = 0
-6 + 2x + (4 * -3 + -2x * -3) + x = 0
-6 + 2x + (-12 + 6x) + x = 0

Reorder the terms:
-6 + -12 + 2x + 6x + x = 0

Combine like terms: -6 + -12 = -18
-18 + 2x + 6x + x = 0

Combine like terms: 2x + 6x = 8x
-18 + 8x + x = 0

Combine like terms: 8x + x = 9x
-18 + 9x = 0

Solving
-18 + 9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 9x = 0 + 18

Combine like terms: -18 + 18 = 0
0 + 9x = 0 + 18
9x = 0 + 18

Combine like terms: 0 + 18 = 18
9x = 18

Divide each side by '9'.
x = 2

Simplifying
x = 2

See similar equations:

| 3j=81 | | 5x(3+7)=13 | | 6*n=42 | | 48/=4 | | n*11=88 | | abs(6+2x)=8 | | x^2-4y^2-2x-16y-31=0 | | 44/n=11 | | 4x+15=60 | | 0,60=(10,80-3)/(x*4,56) | | 0.60=(10.80-3)/(x*5.56^2) | | k/-51=65 | | 3x^2-1X=47 | | Log(x+20)=0 | | 2n-5=4n+9 | | 2x-29y=-5 | | f(x)=-x^2+6x+4 | | 58-y=209 | | 11x+1=5(x+5) | | -u+189=145 | | 2(1.6y)-1.33=-y+4.13 | | 59-4x=-72-7x | | -u+127=213 | | 3x+8=-17 | | -0.2m+13=0.2m-6 | | 8=2c+24 | | 2(y^2-66+13y)=0 | | 2.68d+2.04=-1.02d+6.1 | | -9x/12=3/4 | | 1x+7-7x=6x+2-2x | | xy+x+y=0 | | bitxh=fr |

Equations solver categories